2012
DOI: 10.1200/jco.2012.30.15_suppl.4098
|View full text |Cite
|
Sign up to set email alerts
|

Lenalidomide for second-line treatment of advanced hepatocellular cancer (HCC): A Brown University Oncology Group phase II study.

Abstract: 4098 Background: Lenalidomide inhibits fibroblast growth factor (FGF), vascular endothelial growth factor (VEGF) and multiple tumor growth pathways. There is no standard of care for patients who progress after sorafenib. Therefore, we performed a phase II study to determine the activity of lenalidomide in second-line HCC therapy. Methods: Patients with advanced HCC who progressed on or were intolerant to sorafenib were eligible. Prior chemoembolization, RFA, or surgery were allowed. Eligibility criteria also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…In this study, we found that lenalidomide has modest anti‐tumour efficacy as second‐line therapy for patients with advanced HCC, and the safety profile is similar to those previously reported . The response rate and survival found in our study were consistent with those reported in the phase 2 trial conducted in the USA . Early α‐fetoprotein response may serve as a surrogate efficacy marker, as previously reported for various targeted therapies for HCC .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this study, we found that lenalidomide has modest anti‐tumour efficacy as second‐line therapy for patients with advanced HCC, and the safety profile is similar to those previously reported . The response rate and survival found in our study were consistent with those reported in the phase 2 trial conducted in the USA . Early α‐fetoprotein response may serve as a surrogate efficacy marker, as previously reported for various targeted therapies for HCC .…”
Section: Discussionsupporting
confidence: 90%
“…Both agents are approved for the treatment of multiple myeloma and show anti‐tumour activity in other hematological malignancies. We and other investigators have previously shown the potential efficacy of thalidomide and lenalidomide for the treatment of advanced HCC . In this open‐label phase II clinical trial, we sought to confirm the efficacy and safety of lenalidomide as second‐line therapy for advanced‐stage HCC (BCLC stage C) and searched for potential clinical, molecular and immunological biomarkers to predict treatment efficacy of lenalidomide in HCC.…”
Section: Introductionmentioning
confidence: 99%
“…Lenalidomide was well tolerated, with rare grade 3 toxicities. The PR rate was 15%, including 2 patients with a durable response of 32 and 36 months [16].…”
Section: Trial Informationmentioning
confidence: 94%
“…Liver cancer is the most common malignant liver disease in adults (8). Although the success of its therapy is improving continuously, and there are a variety of therapies, including surgical resection, liver transplantation, radiotherapy and chemotherapy, none has significantly extended the mean 5-year survival of patients with liver cancer (9,10). One of the most important reasons for the high mortality and poor prognosis of patients with liver cancer is that the underlying molecular mechanism is poorly understood.…”
Section: Discussionmentioning
confidence: 99%